Peran Pengasuh Santri dalam Mengatasi Konflik Antar Santri Pondok Pesantren Idrisiyyah Putri - Dalva Qolbiyah, Neng; Deni, Asep; Wisa Belinda, Ulfi (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
The Islamic boarding school environment, inhabited by students with diverse social, cultural, and character backgrounds, has the potential to cause conflict, both within individuals and between individuals and groups. Conflict is an unavoidable part of life's reality and can occur anytime and anywhere. Therefore, the optimal role of student mentors is needed in providing guidance, both individually and in groups, to prevent and resolve conflicts that occur in the Islamic boarding school environment. This study aims to determine the role of student mentors in resolving conflicts between students and identify the factors that cause conflict at the Idrisiyyah Putri Islamic Boarding School. This study uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, while data validity was tested using triangulation of sources, techniques, and time. Conflicts between students are influenced by internal factors, such as the inability to control emotions, irritability, the desire for recognition, and misunderstandings, and external factors originating from the family environment and peer interactions. In this context, student guardians play a crucial role as mediators in resolving conflicts fairly and wisely, as well as educators who instill moral values, tolerance, and social skills in students. Furthermore, guardians play a crucial role in creating a conducive, safe, and comfortable Islamic boarding school environment, allowing students to express their problems and find solutions together.